The Moral Foundations of Public Engagement: Does Political Science, as a Discipline, Have an Ethics?. (May 2020) - Flinders, Matthew; Pal, Leslie A
In recent years, the discipline of political science has been the focus of extensive criticism from observers based both within and beyond the academy. This is reflected in a sizable number of scholars who have called for the discipline to recognize its obligations to the public, and especially to supporting active citizenship, promoting democratic participation and addressing major social challenges. This emphasis on 'making political science matter' has also been stressed beyond the academy as funders, politicians and potential research-users place ever-greater emphasis on incentivizing and rewarding 'impact', 'relevance' and demonstrable 'public value'. The central argument of this article is that what has been missing from this debate is any sense of clarity around whether what is being demanded is greater engagement by political science as a discipline or greater engagement by political scientists as individuals. This raises distinctive questions about the moral foundations and professional ethics of political science which we explore not through a traditional focus on defending or sustaining liberal democracy but through a deeper and more subtle emphasis on the praxis of 'doing' political science.